Measurement properties of painDETECT by average pain severity - Cappelleri JC; Bienen EJ; Koduru V; Sadosky A (Dove Medical Press, 2014)
Joseph C Cappelleri,1 E Jay Bienen,2 Vijaya Koduru,3 Alesia Sadosky4 1Pfizer, Groton, CT, 2Outcomes research consultant, New York, NY, 3Eliassen Group, New London, CT, USA; 4Pfizer, New York, NY, USA Background: Since the burden of neuropathic pain (NeP) increases with pain severity, it is important to characterize and quantify pain severity when identifying NeP patients. This study evaluated whether painDETECT, a screening questionnaire to identify patients with NeP, can distinguish pain severity. Materials and methods: Subjects (n=614, 55.4% male, 71.8% white, mean age 55.5 years) with confirmed NeP were identified during office visits to US community-based physicians. The Brief Pain Inventory – Short Form stratified subjects by mild (score 0–3, n=110), moderate (score 4–6, n=297), and severe (score 7–10, n=207) average pain. Scores on the nine-item painDETECT (seven pain-symptom items, one pain-course item, one pain-irradiation item) range from -1 to 38 (worst NeP); the seven-item painDETECT scores (only pain symptoms) range from 0 to 35. The ability of painDETECT to discriminate average pain-severity levels, based on the average pain item from the Brief Pain Inventory – Short Form (0–10 scale), was evaluated using analysis of variance or covariance models to obtain unadjusted and adjusted (age, sex, race, ethnicity, time since NeP diagnosis, number of comorbidities) mean painDETECT scores. Cumulative distribution functions on painDETECT scores by average pain severity were compared (Kolmogorov–Smirnov test). Cronbach's alpha assessed internal consistency reliability. Results: Unadjusted mean scores were 15.2 for mild, 19.8 for moderate, and 24.0 for severe pain for the nine items, and 14.3, 18.6, and 22.7, respectively, for the seven items. Adjusted nine-item mean scores for mild, moderate, and severe pain were 17.3, 21.3, and 25.3, respectively; adjusted seven-item mean scores were 16.4, 20.1, and 24.0, respectively. All pair-wise comparisons of scores between pain-severity groups showed sizable and statistically significant differences (P<0.0001). Cumulative distribution functions showed distinct separation between severity (P<0.0001). Cronbach's alphas were 0.76 and 0.80 for the nine- and seven-item scales, respectively. Conclusion: This study provides strong psychometric evidence on the validity and reliability of painDETECT for distinguishing average pain severity in patients with NeP. Keywords: neuropathic pain, painDETECT, pain severity, psychometric properties